2021
DOI: 10.1111/dth.14979
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome in patients with Alopecia Areata: A case‐control study

Abstract: The aim of this study was to evaluate metabolic syndrome prevalence in patients with Alopecia Areata compared to controls. Sixty eligible patients with Alopecia Areata and 60 healthy subjects frequency matched for age and sex attending to our referral dermatology clinics from 2015 to 2017 were enrolled. Prevalence of metabolic syndrome and its components were compared between the two groups. Metabolic syndrome was only seen in seven patients (11.67%) and four controls (6.67%) without a significant difference (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 19 publications
(54 reference statements)
0
11
0
Order By: Relevance
“…Abdollahimajd and his colleagues (2021) in Indian population study for AGA described the characteristics and relationship between MetS and CAA plaque. They concluded that there was no significant difference was found in the mean of the cholesterol levels, but two CAA plaques found in the case group which gives a high recommendation to rule out CAA in AGA patients group (Abdollahimajd et al, 2021).…”
Section: Resultsmentioning
confidence: 94%
“…Abdollahimajd and his colleagues (2021) in Indian population study for AGA described the characteristics and relationship between MetS and CAA plaque. They concluded that there was no significant difference was found in the mean of the cholesterol levels, but two CAA plaques found in the case group which gives a high recommendation to rule out CAA in AGA patients group (Abdollahimajd et al, 2021).…”
Section: Resultsmentioning
confidence: 94%
“…Additionally, compared to controls, metabolic syndrome has been reported to be higher in patients with AA 16 . Further, in another study by Abdollahimajd et al, although there was no significant association between AA and metabolic syndrome, some of its components were more prevalent in these patients 17 . Insulin resistance is a component of some metabolic syndrome criteria, playing an essential role in its pathophysiology, 18 and AA patients appear to have increased insulin resistance 19–21 …”
Section: Discussionmentioning
confidence: 95%
“…16 Further, in another study by Abdollahimajd et al, although there was no significant association between AA and metabolic syndrome, some of its components were more prevalent in these patients. 17 Insulin resistance is a component of some metabolic syndrome criteria, playing an essential role in its pathophysiology, 18 and AA patients appear to have increased insulin resistance. [19][20][21] There is evidence that immune responses and hair disorders are directly or indirectly linked to metabolic intermediates and lipids in the cholesterol biosynthesis pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Nasimi et al discovered that 20 of 50 patients (54%) with alopecia areata had metabolic syndrome, a considerably greater rate than the 13 (26%) in controls [163]. In contrast, the frequency of metabolic syndrome was not statistically different between AA patients and healthy people in the research of Abdollahimajd et al; nonetheless, AA patients had higher triglyceride levels and lower HDL cholesterol levels [164].…”
Section: Alopecia Areatamentioning
confidence: 95%